2017
DOI: 10.14260/jemds/2017/1001
|View full text |Cite
|
Sign up to set email alerts
|

Grade 2 Deformity and New Leprosy Cases, an Issue of Concern- A Retrospective, Descriptive Study in a Tertiary Care Hospital

Abstract: BACKGROUNDLeprosy is a chronic infectious disease with neural, skin and upper airway mucosal involvement caused by Mycobacterium leprae. The magnitude of deformity in new leprosy patients measures indirectly the disease transmission in the community and rapidity of case detection. Occurrences of grade 2 deformity in new leprosy cases have been included as one of the indicators for a good control of the disease.The aim of this study is to find out the incidence of grade 2 deformities among new leprosy cases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…This discordance in our study could be explained by the patient profile disparity at the starting of the treatment and the onset of follow-up as patients may not develop multiple nerve trunk enlargement at the beginning and this nerve thickening might be more in patients with complex progression of the disease. Even if in this study the sex and first lesion body part were not found to be statistically significant, the higher rate of disability associated with the male sex in our study was noted by others as well [ 35 ]. It can be explained by the fact that males are more prone to trauma to hands and feet as part of their occupation.…”
Section: Resultscontrasting
confidence: 68%
“…This discordance in our study could be explained by the patient profile disparity at the starting of the treatment and the onset of follow-up as patients may not develop multiple nerve trunk enlargement at the beginning and this nerve thickening might be more in patients with complex progression of the disease. Even if in this study the sex and first lesion body part were not found to be statistically significant, the higher rate of disability associated with the male sex in our study was noted by others as well [ 35 ]. It can be explained by the fact that males are more prone to trauma to hands and feet as part of their occupation.…”
Section: Resultscontrasting
confidence: 68%
“…The higher rate of disability associated with male sex in our study was noted by others as well. [6789] It can be explained by the fact that males are more prone to trauma to hands and feet as part of their occupation. A statistically significant association noted for disability and age above 45 years is in accordance with several other studies.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Even if in this study sex and first lesion body part were not found to be statistically significant, others have noticed the greater rate of impairment connected with male sex and it was in our study as well. 14 It can be explained by the fact that males are more prone to hand and foot damage as a result of their work. 15 Described the most common location of disability as the feet, whereas others, like ourselves, identified the hands as the most commonly involved region in terms of disability.…”
Section: Discussionmentioning
confidence: 99%